Comparative susceptibilities of human embryonic fibroblasts and HeLa cells for isolation of human rhinoviruses. - Arruda, E (1996)
The recovery of human rhinovirus (HRV) from nasal washings and nasal and pharyngeal swabs from volunteers with naturally acquired colds was compared in different cell types. Human embryonic lung fibroblast (HELF) strain WI-38 (sensitivity, 61 to 84%) and HeLa-I, an HRV-susceptible HeLa clone (sensitivity, 86 to 94%), were the most sensitive cell types used. HELF-WI-38 cells showed a cytopathic effect earlier than the other cells used, and the different strains of HRV-susceptible HeLa cells varied in their sensitivities for HRV isolation. HRV was detected in a single cell type in 20 to 35% of the positive samples, suggesting that use of a combination of different HRV-susceptible cell lines is the best approach for the recovery of HRV. Although nasal washings tended to yield more HRV isolates than nasal and pharyngeal swabs, the two sampling methods were not found to be significantly different.